Pelaksanaan Program Kota Tanpa Kumuh di Kota Padang - Musral Lingga Wati; Yusnanik Bachtiar (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2019)
Abstract Slum is a problem that has long since occurred and also become the main obstacle to the development of large cities, including one of Padang's right city in the village of Dadok Tunggul Hitam and village of Alai Parak Kopi. In line with the problem, the Ministry of Public Works and housing of the Indonesian people created a national slum handling strategy program called the Program Kota Tanpa Kumuh (Kotaku). This Program is in the implementation of Dadok Tunggul Hitam and Alai Parak Kopi. This research aims to meet the implementation of the Ungrungy City program, community participation, and constraints during its implementation. The type of research used is Field research with a descriptive method through a qualitative approach. The informant of this research is a subdistrict apparatus, Kelurahan, Community Empowerment Institute (LPM), an ungrungy city Program activists and elements of society. Data collection techniques through observation, interviews, and documentation. The results of this research show that the implementation of the Ungrungy City program in the two villages is already running well, as well as the participation of its significant community, as well as the constraints are also not so much, only partly People do not understand the purpose of the program of the Ungrungy city because there is busy work. Key words: Program Kota Tanpa Kumuh, Community Participation